Improvement of the enterprise infrastructure evaluation method - Levykin, Viktor; Iuriev, Ivan (Technology audit and production reserves, 2018)
The object of research is the enterprise infrastructure. The main task of enterprise infrastructure is ensuring the availability of IT services and software for users and support business growth. The main disadvantage of the existing process of evaluating the infrastructure of an enterprise is identification of its main components. One of the most problematic places is the evaluation of the enterprise infrastructure to determine the impact of the introduction of a new IT service in a context of continuous changes in functional requirements of end-users. Based on the results of the analysis of the infrastructure evaluation problems and the existing variants of the term "enterprise infrastructure", the main elements of the enterprise infrastructure are identified. It is proposed to define the infrastructure of the enterprise as a set of interconnected IT services, information and communication technologies integrated by the computer network of the enterprise. In the course of the research, the analysis of the basic methods of evaluating the infrastructure of the enterprise was carried out, their advantages and disadvantages were determined. As a result of the analysis of the enterprise infrastructure evaluation process, an improved method for evaluating the infrastructure of the enterprise was proposed. The proposed method, in contrast to the existing ones, combines quantitative cost evaluation and a qualitative evaluation of the components of the updated infrastructure of the enterprise, allowing a comprehensive evaluation of its infrastructure and formulating recommendations for the application of the selected IT service. The advantage of the proposed method is that it provides the opportunity to form a preliminary evaluation of the planned changes in the infrastructure of the enterprise and thus refuse to make changes in the event of their low efficiency. It is noted that any modification of the infrastructure of an enterprise leads to a change in the indicator of its quality evaluation. Consequently, the detection of the dynamics of the indicator of quality evaluation will allow controlling the quality of the infrastructure of the enterprise. The accumulated statistics makes it possible to identify trends and, on the basis of their analysis, make timely decisions about the need for changes in the infrastructure of the enterprise in order to adapt it to the new conditions. The results of the enterprise infrastructure evaluation can also be used to develop management decisions for the development and improvement of the enterprise.